1996
DOI: 10.1002/(sici)1097-4601(1996)28:10<721::aid-kin2>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase ozonolysis of ethene in the presence of hydroxylic compounds

Abstract: Ozonolysis of C2H4 was carried out at 295 K in 730 torr synthetic air in the concentration ranges of [O3]0 = 1.9–8.2 ppm and [C2H4]0 = 4.0–15.0 ppm, in the absence and presence of the added HCOOH (1 ppm), CH3COOH (1–10 ppm), and CH3OH (36–100 ppm). In the absence of the added compounds, a nearly complete analysis of the reaction products was achieved, with the yields expressed relative to the converted C2H4: HCHO 0.98, CO 0.26, CO2 0.18, HCOOH 0.05, and the sum of formic acid anhydride (FAN) and hydroperoxymet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
130
3
9

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(157 citation statements)
references
References 10 publications
15
130
3
9
Order By: Relevance
“…Experimental highpressure limit rates are unknown for these reactions. Conditions for known experiments are around the standard conditions of 298 K and 1 atm [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Considerations at higher temperatures and pressures have never been made for these reactions, but will be considered here in the low-temperature combustion of dimethyl ether.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental highpressure limit rates are unknown for these reactions. Conditions for known experiments are around the standard conditions of 298 K and 1 atm [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Considerations at higher temperatures and pressures have never been made for these reactions, but will be considered here in the low-temperature combustion of dimethyl ether.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the ÁH z 298 ¼ 69:6 kcal mol À1 ((CCSD(T)/6-311þG(3df, 3pd)) result calculated by Cremer et al [15] (from the lowest energy configuration of formic acid). A summary of all reaction rate constants is given in Table 4 [40][41][42], HC(¼O)OH [40,49,52,54,82], SO 2 [40,83], NO [84], NO 2 [84], CO [40], and CO 2 [40]. Theoretical calculations on a subset of these possible bimolecular reactions (CH 2 OO with H 2 O, H 2 C¼O, HC(¼O)OH, SO 2 , and CO 2 ) have been done only recently.…”
mentioning
confidence: 99%
“…Fenske et al, 2000). Reaction of CH 2 OO with formic acid, HCOOH, yielding to production of hydroperoxymethyl formate was demonstrated by Neeb et al (1995Neeb et al ( , 1996, with follow-up studies by Thamm et al (1996) and Hasson et al (2001b). Neeb et al (1997) showed that the rate coefficient for the above reaction is relatively large (14 000-fold) in comparison to the reaction rate coefficient for CH 2 OO + water.…”
mentioning
confidence: 95%
“…Due to the relatively long lifetime of sCI, bimolecular reactions of sCIs with several compounds like water vapour, SO 2 , carbonyls, organic acids, etc., are also possible (e.g. Neeb et al, 1996Neeb et al, , 1997Johnson, 2001;Welz et al, 2012Welz et al, , 2014Mauldin III et al, 2012;Berndt et al, 2012Berndt et al, , 2014aTaatjes et al, 2012Taatjes et al, , 2013. These reactions can potentially be fast enough to contribute significantly to the atmospheric oxidation capacity.…”
mentioning
confidence: 99%
“…ROO·와 HO 2 반응으로 organic hydroperoxide wacki et al, 2012;Atkinson and Arey, 2003;Benson, 1965). Alkoxy radical (RO·) 역시 peroxy radical (ROO·) Taatjes et al, 2013;Mauldin Iii et al, 2012;Welz et al, 2012;Neeb et al, 1996;Hatakeyama and Akimoto, 1994;Lai et al, 1990). 두 번째 경로는 peroxide channel (그림 3)인데, isomerization으로 δ 위치에 있는 탄소에 결합해 있는 수소원자 를 빼앗아서 (또는 1,4 hydride shift) organic hydroper-…”
Section: 연구 동향unclassified